2018
DOI: 10.1093/mmy/myy118
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of guideline recommendations for prognosis in patients with candidemia

Abstract: We aimed to analyze whether the lack of inclusion of specific recommendations for the management of candidemia is an independent risk factor for early and overall mortality. Multicenter study of adult patients with candidemia in 13 hospitals. We assessed the proportion of patients on whom nine specific ESCMID and IDSA guidelines recommendations had been applied, and analyzed its impact on mortality. 455 episodes of candidemia were documented. Patients who died within the first 48 hours were excluded. Sixty-two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
0
31
0
1
Order By: Relevance
“…Garnacho-Monterio et al, Kato et al, and Papadimitriou-Olivgeris et al identified that appropriate empirical antifungal treatment was related to better prognosis [12,39,40]. Indeed, lack of inclusion of European Society of Clinical Microbiology and Infectious Disease (ESCMID) and Infectious Diseases Society of America (IDSA) guideline recommendations was an independent risk factor for a higher early and overall mortality [4]. In the same way, Keighley et al found that age > 65 years, ICU admission, chronic organ dysfunction, preceding surgery within 30 days, haematological malignancy, source of candidaemia, and antibiotic therapy for ≥10 days were independent risk factors for candidemia mortality, which served to develop a risk predictive score [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garnacho-Monterio et al, Kato et al, and Papadimitriou-Olivgeris et al identified that appropriate empirical antifungal treatment was related to better prognosis [12,39,40]. Indeed, lack of inclusion of European Society of Clinical Microbiology and Infectious Disease (ESCMID) and Infectious Diseases Society of America (IDSA) guideline recommendations was an independent risk factor for a higher early and overall mortality [4]. In the same way, Keighley et al found that age > 65 years, ICU admission, chronic organ dysfunction, preceding surgery within 30 days, haematological malignancy, source of candidaemia, and antibiotic therapy for ≥10 days were independent risk factors for candidemia mortality, which served to develop a risk predictive score [41].…”
Section: Discussionmentioning
confidence: 99%
“…This infection is associated with considerable morbidity and mortality, including prolonged hospital stays and increased healthcare costs, with 30% to 50% occurring in patients in the intensive care unit (ICU) [3]. Importantly, the crude candidemia mortality ranges from approximately 22% to 75%, despite advances in diagnosis and therapy [4,5,6,7,8]. Despite advancements such as effective broad-spectrum antifungals and recent management guidelines, the incidence of candidemia has doubled over the past two decades [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of septic shock is only collaterally mentioned in reports on candidemia in the general populations and it ranges from 12.9 to 49.0% in recent studies [16][17][18]. However, only three series have specifically focused on the incidence of septic shock among candidemic patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 Microbiology Unit, Azienda Sanitaria Universitaria Integrata Santa Maria della Misericordia, Udine, Italy. 17 Medicine Department School of Medicine, Universidad Complutense de Madrid, Madrid, Spain. 18 CIBER Enfermedades Respiratorias-CIBERES (CB06/06/0058), Udine, Spain.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Recomendaciones y grados de evidencia de las técnicas alternativas al cultivo para el diagnóstico de candidemia morbimortalidad de la candidemia, es muy elevada, pudiendo llegar a tener una tasa de mortalidad mayor de 40% en pacientes en UCI. Un retraso en el inicio del tratamiento se ha relacionado con un incremento de la mortalidad a los 30 y 90 días del diagnóstico(17,42,53,107,131, 132). Un diagnóstico precoz resulta difícil dado que las técnicas diagnósticas que existen en la mayoría de los hospitales requieren tiempo y su valor predictivo positivo es bajo.…”
unclassified